2023
DOI: 10.1037/emo0001120
|View full text |Cite
|
Sign up to set email alerts
|

Desired sadness, happiness, fear and calmness in depression: The potential roles of valence and arousal.

Abstract: Prior research has shown that clinically depressed individuals are somewhat more motivated to feel sadness and less motivated to feel happiness than nondepressed individuals are. However, what underlies these patterns is not yet clear, as people may be motivated to experience positive (vs. negative) valence, high (vs. low) arousal, or discrete emotions. To test these possibilities, we assessed the motivation to experience emotions that capture different combinations of positive and negative valence and high an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Consistent with previous research on motivation for emotions in depression as a function of valence (Mizrahi Lakan, Millgram, & Tamir, 2022), items represented prototypical pleasant emotions characterized by low (i.e., calm) and high (i.e., happy) arousal, and prototypical unpleasant emotions characterized by low (i.e., sad) and high (i.e., anxious) arousal. Participants rated how much they wanted to feel happy and calm (e.g., “In the past 2 hr, how much did you want to feel happy?”; 1 = not at all , 9 = to a large extent ; ω Between = 0.85, ω Within = 0.63), and how much they wanted to feel sad and anxious (e.g., “In the past 2 hr, how much did you want to feel sad?”; 1 = not at all , 9 = to a large extent ; ω Between = 0.72, ω Within = 0.61) 6…”
Section: Methodssupporting
confidence: 78%
“…Consistent with previous research on motivation for emotions in depression as a function of valence (Mizrahi Lakan, Millgram, & Tamir, 2022), items represented prototypical pleasant emotions characterized by low (i.e., calm) and high (i.e., happy) arousal, and prototypical unpleasant emotions characterized by low (i.e., sad) and high (i.e., anxious) arousal. Participants rated how much they wanted to feel happy and calm (e.g., “In the past 2 hr, how much did you want to feel happy?”; 1 = not at all , 9 = to a large extent ; ω Between = 0.85, ω Within = 0.63), and how much they wanted to feel sad and anxious (e.g., “In the past 2 hr, how much did you want to feel sad?”; 1 = not at all , 9 = to a large extent ; ω Between = 0.72, ω Within = 0.61) 6…”
Section: Methodssupporting
confidence: 78%
“…Related to this point, the present research targeted healthy individuals who generally did not want to experience intense unpleasant emotions. Future research should test whether the current findings replicate in unhealthy samples (e.g., those suffering from clinical disorders), where the mean levels of unpleasant emotion goals tend to be higher, in comparison (e.g., Millgram et al, 2015; Millgram, Joormann, et al, 2019; Millgram, Sheppes, et al, 2019; Mizrahi Lakan, Millgram, & Tamir, 2023). Furthermore, future research should directly test our interpretation of the results, as well as other potential interpretations.…”
Section: Discussionmentioning
confidence: 87%
“…Pursuing more pleasant emotion goals and less unpleasant emotion goals may be beneficial. For instance, the pursuit of more intense unpleasant emotionss and less intense pleasant emotions have been linked to depression (e.g., Millgram et al, 2015; Mizrahi Lakan, Millgram, & Tamir, 2023). Thus, a desire for more unpleasant emotions or less pleasant emotions, in general, is related to worse mental health.…”
Section: Emotion Goalsmentioning
confidence: 99%
“…Evaluations of valence (i.e., pleasantness vs. unpleasantness) and arousal (i.e., low intensity vs. high intensity) represent key components of affective experiences and can be particularly relevant and useful in understanding the emotional burden of loneliness and its association with mental health outcomes. Research has shown that valence and arousal can differentiate between different emotional experiences at a neural level [ 14 , 15 ], and predict different mental health outcomes [ 16 ]. For instance, people with depression process and respond to emotional stimuli different than people without depression, and emotional valence and arousal modulate this process [ 17 ].…”
Section: Introductionmentioning
confidence: 99%